Quantitative Proteome Analysis of Jatropha curcas L. Genotypes with Contrasting Levels of Phorbol Esters. Issue 14 (2nd July 2020) - Farias, Andreza Raquel Barbosa de; Almeida, Natália P.; Domont, Gilberto B.; Nogueira, Fábio C. S.; Campos, Francisco A. P.
Abstract: The phorbol esters in the seeds of Jatropha curcas are a major hindrance to the full exploitation of the potential of this oil crop as a source of raw material for the production of biodiesel. Here, various quantitative proteomic strategies are used to establish the proteomes of roots, leaves, and endosperm of two genotypes of J. curcas with contrasting levels of phorbol esters in the seeds. In total 4532, 1775, and 503 proteins are identified respectively in roots, leaves, and endosperm, comprising 5068 unique proteins; of this total, 185 are differentially abundant in roots, 72 in leaves, and 20 in the endosperm. The biosynthetic pathways for flavonoids and terpenoids are well represented in roots, including the complete set of proteins for the mevalonate and non‐mevalonate/Deoxyxylulose 5‐Phosphate pathways, and proteins involved in the branches which lead to the synthesis tricyclic diterpenoids and gibberellins. Also, casbene synthase which catalyzes the first committed step in the biosynthesis of tigliane‐type diterpenes is identified in roots of both genotypes, but not in leaves and endosperm. This dataset will be a valuable resource to explore the biochemical basis of the low toxicity of Jatropha genotypes with low concentration of phorbol esters in the seeds.